Les établissements perchés de l’Auvergne (ive-viie s. apr. J.-C.) : de nouvelles formes d’habitat groupé - Sandra Chabert; Damien Martinez (Gallia)
The resurgence of hilltop settlements that began in the Late Antiquity in Gaul is now at the heart of Roman period and medieval archaeological research. For a long time this subject was considered anecdotal, however it is now being reconsidered and incorporated into the discourse on such new forms of concentrated settlement. The recent studies in the Auvergne region, inspired by earlier research developed in the 60’s, fit in the movement of founding studies that were initiated in the South and North-East of France. The project undertaken for the last few years on the site of La Couronne Molles (Allier), has shown that field work is vital to be able to address the reality of this new settlement pattern, often present on lesser known sites. The first conclusions that we can bring are based on a series of sites that share common general characteristics (topographical context, fortification), and yet have different forms and functions. On another hand, the archeological material, particularly the pottery, shows that such sites are far from isolated. On the contrary, they are perfectly integrated in the commercial networks that supplied the Arverne city at the end of the Antiquity.